2016
DOI: 10.1002/da.22521
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Psychosocial Functioning and Health-Related Quality of Life Following Exercise Augmentation in Patients With Treatment Response but Nonremitted Major Depressive Disorder: Results From the Tread Study

Abstract: BACKGROUND Functional impairments often remain despite symptomatic improvement with antidepressant treatment, supporting the need for novel treatment approaches. The present study examined the extent to which exercise augmentation improved several domains of psychosocial functioning and quality of life among depressed participants. METHODS Data were collected from 122 partial responders to antidepressant medication. Participants were randomized to either high (16 kilocalories per kilogram of weight per week [K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 73 publications
1
32
0
Order By: Relevance
“…These findings extend previous studies reporting substantial improvement in psychosocial function with a variety of treatments [7–13, 48]. They also add to an emerging literature that suggests that at least a subgroup of depressed individuals realize functional improvements early in the course of antidepressant treatment, and these early changes in work productivity and psychosocial function predict future clinical course [27].…”
Section: Discussionsupporting
confidence: 84%
“…These findings extend previous studies reporting substantial improvement in psychosocial function with a variety of treatments [7–13, 48]. They also add to an emerging literature that suggests that at least a subgroup of depressed individuals realize functional improvements early in the course of antidepressant treatment, and these early changes in work productivity and psychosocial function predict future clinical course [27].…”
Section: Discussionsupporting
confidence: 84%
“…Full description of these measures have been published previously (Greer et al, 2016; Rethorst et al, 2013a; Rethorst et al, 2013b; Suterwala et al, 2016; Toups et al, 2011; Trivedi et al, 2011; Trivedi et al, 2006a). These variables were selected based on the results of these previously published findings and other factors that have been associated with treatment outcomes in depression (Sotsky et al, 1991; Trivedi et al, 2006b; Warden et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Critically, however, there is scant information concerning the effects of exercise on non-mood outcomes, including social and cognitive functioning and quality of life, in patients who do not respond to first-line therapies,20 or who experience recurrent episodes and ongoing functional impairment,12 14 21 even after mood symptoms have improved 22 23. Here, only a handful of studies reported improvements in depressive symptoms24–26 and psychosocial functioning and quality of life27 in treatment-resistant clinical populations. Finally, there is a paucity of research examining the impact of exercise on outcomes in patients with BD 28.…”
Section: Introductionmentioning
confidence: 99%